THE NEXUS BETWEEN GROWTH AND UNEMPLOYMENT RATE IN PAKISTAN: DOES OKUN’S LAW EXIST? - Muhammad Salahuddin Ayyubi; Humna Ahsan; Ayesha Anwar; Asad Elahi Khan; Muhammad Ghulam Shabeer (International Journal of Contemporary Issues in Social Sciences, 2024)
This research is an in-depth examination of the link between the unemployment rate and output growth in Pakistan. The study begins with a background discussion of Okun’s law, the Gross Domestic Product (GDP), unemployment, and the situation in the three main sectors of Pakistan. A comprehensive literature review is then presented, which includes authors’ interpretations of studies related to Okun’s law in Pakistan and other developed nations. The literature review is followed by a discussion of the methods used to determine the Okun coefficient, including the use of the Autoregressive Distributed Lag (ARDL) model to examine the link between unemployment and output growth. Additionally, to understand the impact of the growth rate of the three main sectors on the unemployment gap, the Ordinary Least Squares (OLS) technique was used as all the variables were found to be stationary at the level. The study provides promising results, revealing a negative relationship between the output growth gap and the unemployment gap. The findings of this study contribute to a better understanding of the dynamics of unemployment and output growth in Pakistan and provide valuable insights for policymakers and economists.